The Development of Interactive Media Based on the Quizizz Application for Science Subject - Heri Supriyadi; Yusuf Hartono; Riswan Jaenudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This study aims to produce interactive media based on the Quizizz application that is valid, practical, and effective for fifth-grade science subjects at SD Negeri 7 Lahat. This study involved 15 fifth-grade students. The study uses the Hannafin and Peck development model consisting of three stages: needs analysis, design–development, and implementation–evaluation. Based on the results of the needs analysis, it shows that the limitations of learning media mean that teachers need media that can support the learning process. Meanwhile, students are less motivated and have difficulty understanding science lesson concepts when delivered using conventional methods. The results of validation by experts show that this media is very valid, with a score of 98% for material, 94% for media, and 84% for language. The practicality test was carried out through one-to-one and small group tests with a score of 96.22%. The effectiveness test results showed an increase in learning outcomes from an average pretest score of 53.67 to 88.00 in the posttest, with an N-Gain value of 0.78, which is considered high. Thus, the Quizizz app-based interactive media was declared feasible and effective for improving fifth-grade elementary school students' science learning outcomes.